Can Serum ICAM 1 distinguish pancreatic cancer from chronic pancreatitis? - mohamed, amal; Saad, Yasmine; Saleh, Doaa; Elawady, Rehab; Eletreby, Rasha; Kharalla, Ahmad S; Badr, Eman (Asian Pacific journal of cancer prevention : APJCP, 2016)
Background and aim: Pancreatic cancer is the fourth leading cause of cancer-related death worldwide, with an overall 5-year survival of <5% mainly due to presence of advanced disease at time of diagnosis. Therefore development of valid biomarkers to diagnose pancreatic cancer in early stages is an urgent need. This study concerned the sensitivity and specificity of serum ICAM 1 versus CA 19-9 in differentiation between pancreatic cancer and healthy subjects and acohort of patients with chronic pancreatitis with a focus on assessing validity in diagnosis of early stages of pancreatic cancer. Methods: A cohort of 50 patients with histologically diagnosed pancreatic tumors, 27 patients with chronic pancreatitis, and 35 healthy controls were enrolled. Serum samples for measurement of CA19-9 and I-CAM 1 were obtained from all groups and analyzed for significance regarding diagnosis and disease stage. Results: At a cut off value of (878.5 u/ml) I-CAM 1 had 82% and 82.26% sensitivity and specificity for differentiation between cancer and non-cancer cases, with higher sensitivity and specificity than CA19-9 at different cut offs (CA19-9 sensitivity and specificity ranged from 64-80% and 56.4 – 61.2% respectively). The AUC was 0.851 for I-CAM and 0.754 for CA19-9. Neither of the markers demonstrated significance for distinguishing between early and late cancer stages. Conclusion: ICAM 1 is a useful marker in differentiation between malignant and benign pancreatic conditions, and superior to CA19-9 in this regard. However, neither of the markers can be recommended for use in differentiation between early and late stage pancreatic cancers.